Theory and applications of satisfiability testing -- SAT 2017 : 20th International Conference, Melbourne, VIC, Australia, August 28-September 1, 2017, Proceedings /: 20th International Conference, Melbourne, VIC, Australia, August 28-September 1, 2017, Proceedings. (2017) - Unknown
No abstract available